Scaffolds’ production based on calcium aluminate blends and their biological properties - de Las Nieves González Vicuna, Iranel (2019)
Purpose: Scaffolds are artificial structures that provide a temporary template to withstand mechanical loads in vivo during the process of bone regeneration. They should present a highly porous three-dimensional structure with an interconnected network of pores for the tissue growth and the transport of nutrients and metabolic residues. Additionally, scaffolds must be easily manufactured in different shapes and sizes. Methods: A 4 wt% of additives (alumina, zirconia, zinc oxide, hydroxyapatite, or tricalcium phosphate) was added to CAC (calcium aluminate cement), and these blends were used for scaffolds preparation via polymeric sponge replica. Aqueous suspensions were prepared with different solid contents. Sponges impregnated with 55 wt% solid were evaluated for the decomposition temperature by thermogravimetric analysis. The scaffolds microstructures were characterized by scanning electron microscopy and mercury intrusion porosimetry. The relative density was also calculated considering the theoretical density. The scaffolds (60 wt%) were characterized by cytotoxicity assay, total protein content, alkaline phosphatase activity, mineralized bone-like nodule formation, and cell adhesion. Results: The blends prepared with 60 and 55 wt% solid were most suitable for sponge impregnation, resulting in scaffolds with higher fraction of open porosity. The tricalcium phosphate blends presented the best results regarding mineralized nodules. Conclusion: The MTT tests and osteoblast cells adhered to the scaffolds provided predictive evidence of biocompatibility of the material which, associated with the satisfactory results obtained in the cell differentiation tests (ALP), suggested that the scaffolds developed are promising materials. Additionally, all scaffolds allowed the mineralized matrix formation which is a key issue for osteogenesis.